2018
DOI: 10.1089/end.2017.0785
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Single-Use Digital Flexible Ureteroscopes: A Practical Comparison for a Patient-Centered Approach

Abstract: LithoVue outperformed the other ureteroscopes in terms of optical resolution, field of view, deflection capacity, and irrigation flow with larger instruments. Pusen is the lighter scope and showed better results in terms of irrigation when no instruments are in place. Flex-X was superior in terms of color representation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 16 publications
0
50
0
2
Order By: Relevance
“…Despite good clinical results in those early trials, there has been no continuity in this research of late, probably due to the ever-evolving design simplicity of newer models. In their latest publication, Marchini et al [12] compare the Pusen TM scope against the Lithovue TM and the Flex-X 2TM ureteroscope (Karl Storz, Germany). Both disposable scopes showed similar flow rates with a laser fiber or Fr 1.3 basket in the working channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite good clinical results in those early trials, there has been no continuity in this research of late, probably due to the ever-evolving design simplicity of newer models. In their latest publication, Marchini et al [12] compare the Pusen TM scope against the Lithovue TM and the Flex-X 2TM ureteroscope (Karl Storz, Germany). Both disposable scopes showed similar flow rates with a laser fiber or Fr 1.3 basket in the working channel.…”
Section: Discussionmentioning
confidence: 99%
“…Both disposable scopes showed similar flow rates with a laser fiber or Fr 1.3 basket in the working channel. Lithovue TM had the best image resolution, while the Pusen TM was the lightest scope and thus easy to handle [12]. In their in vitro study, Tom et al [6] have shown that 2 of the newest instruments (YC-FR-A and the NeoFlex) have lost a significant part of their deflection with instruments placed in the working channel.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report that, in average, a digital ureteroscope is used 21 times before requiring repair, while the average fiberoptic ureteroscope is only used 6 to 15 times before going back to the manufacturer 26,27 . In a recent study by Legemate et al 23 , permanent digital scopes had a slightly longer longevity (mean 27 cases; 20-56) compared to fiber optic flexible ureteroscopes (mean 24 cases; 10-37). However, a wider look at all published literature reveal that new flexible scopes may last as long as 5 to 159 cases .…”
Section: Longevity Of Digital Optical New and Refurbished Flexible mentioning
confidence: 91%
“…There are many single‐use digital fURS already on the market, including LithoVue (Boston Scientific, Marlborough, MA, USA), PU3022A (Pusen, Zhuhai, China), Polyscope (Lumenis, Yokneam, Israel, Polydiagnost, Hallbergmoos, Germany), Semi‐Flex Scope (Maxiflex, Los Angeles, CA, USA), FlexoVue (Cook Medical, Bloomington, IN, USA) and Yc‐FR‐A (YouCare Tech, Wuhan, China) . In vitro testing has shown that single‐use scopes have equivalent optics, deflection ability and working channel flow rates to more expensive reusable scopes …”
Section: Introductionmentioning
confidence: 99%
“…11 In vitro testing has shown that single-use scopes have equivalent optics, deflection ability and working channel flow rates to more expensive reusable scopes. [12][13][14][15][16][17] In vivo testing has been limited. A European multicenter evaluation of the single-use LithoVue in 40 procedures found that operators rated the image quality as "good" or "very good" in 95% of cases.…”
Section: Introductionmentioning
confidence: 99%